(untitled) (Research, Society and Development, 2021)
Management with synthetic fungicides in the control of phytopathogens in viticulture can cause environmental pollution and contamination with residues in grape cluster. The objective of this study was to verify the effect of aqueous cinnamon extract on the in vitro and in vivo control of Plasmopara viticola on catalase activity on ‘Isabel Precoce’ vines. The treatments used were: aqueous cinnamon extract (ACE) at concentrations of 0.12; 0.25 and 0.50% plus 0.25% vegetable oil (VO); being the standard treatments VO (0.25%), Bordeaux mixture 1:1:100 (lime: copper sulfate: water) and water only. The germination tests of P. viticola sporangia were carried out in incubation periods of 4 and 24 hours of the pathogen in contact with the treatments. In addition, the area under the disease progress curve (AUDPC) and the activity of the catalase enzyme were estimated in plants grown in the greenhouse. The results indicated that the treatments with 0.12%, 0.25% and 0.5% ACE with VO reduced the germination of P. viticola. In relation to the AUDPC, the 0.25% dose of VO associated ACE reduced 65% and 67% in leaf discs and vines in the greenhouse, respectively. This fact is related to the induction of CAT activity provided by this dose in the periods of 2HBA, 2HAI and 4HAI. Thus, it can be said that the ACE associated with VO can be used to control the downy mildew of the ‘Isabel Precoce’ vine.